The effect of propaganda on elections: Evidence from the post-Reconstruction South - Paul Winfree (Queen's University Centre for Economic History (QUCEH), 2022)
Newspapers in the post-Reconstruction South disseminated propaganda accusing Black voters of excessive public corruption. This paper analyzes new data showing that propaganda influenced election outcomes by weakening biracial political coalitions that challenged the Democratic Party immediately before the adoption of new constitutions legally disenfranchising Black voters. These new constitutions reinforced Democratic control of Southern governments that lasted decades into the twentieth century. Specifically, I find evidence that insinuations of public corruption motivated voters to the polls and split the support for biracial coalitions that may have challenged control of the Democratic Party. I also find evidence that large changes in exposure to propaganda were needed to influence election outcomes when voters were routinely exposed to propaganda.
Keywords: D73; N11; N41; N91; 330; disenfranchisement; corruption; election outcomes; Reconstruction; Jim Crow; media bias